2005
DOI: 10.1007/s00417-004-0912-0
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, open-label, dose-escalating study of low molecular weight heparin during repeat vitrectomy for PVR and severe diabetic retinopathy

Abstract: Enoxaparin dose escalation did not result in a dose-dependent increase in acute side effects. The establishment of a well-tolerated dose of enoxaparin during repeat vitrectomy for PVR and severe diabetic retinopathy (6.0 IU/ml) provides a foundation for future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
0
4
0
2
Order By: Relevance
“…One very striking example of this is delineated in a recent article by Sullu et al [23] describing how PPV may decrease the resistive index and improve blood flow through the retinal vessels. Some investigators have reported the application of intravitreal heparin infusion as an aid to removing clotting preretinal hemorrhage intraoperatively [24], as well as the use of low molecular weight heparin (enoxaprin) in the infusion to help decrease the formation of postvitrectomy fibrin [27]. Others have introduced the idea of perfluorocarbon-perfused PPV, which may offer advantages over Balanced Salt Solution infusion in terms of immiscibility with bodily fluids, ability to transport oxygen and gravitational forces [28].…”
Section: Vitrectomy Then and Nowmentioning
confidence: 97%
“…One very striking example of this is delineated in a recent article by Sullu et al [23] describing how PPV may decrease the resistive index and improve blood flow through the retinal vessels. Some investigators have reported the application of intravitreal heparin infusion as an aid to removing clotting preretinal hemorrhage intraoperatively [24], as well as the use of low molecular weight heparin (enoxaprin) in the infusion to help decrease the formation of postvitrectomy fibrin [27]. Others have introduced the idea of perfluorocarbon-perfused PPV, which may offer advantages over Balanced Salt Solution infusion in terms of immiscibility with bodily fluids, ability to transport oxygen and gravitational forces [28].…”
Section: Vitrectomy Then and Nowmentioning
confidence: 97%
“…Intravitreal heparin may be injected to remove pre-retinal clotted blood[ 64 ] and low-molecular-weight heparin (enoxaparin) has been added to the infusion bottle to reduce the formation of post-vitrectomy fibrin. [ 77 ]…”
Section: Managementmentioning
confidence: 99%
“…Moreover, low molecular weight heparin has been shown to reduce postoperative fibrin formation after vitrectomy, in a rabbit model, with fewer haematological complications compared with non-fractionated heparin [49]. These findings were recently confirmed in patients with advanced PVR or severe diabetic retinopathy [50,51].…”
Section: Drug Treatment Of Pvrmentioning
confidence: 88%